A boundary field induced first-order transition in the 2D Ising model: numerical study - Bittner, Elmar; Janke, Wolfhard (Journal of physics. A, Mathematical and theoretical, 2008)
In a recent paper, Clusel and Fortin ( 2006 J. Phys. A: Math. Gen. [/0305-4470/39/5/001] 39 995 ) presented an analytical study of a first-order transition induced by an inhomogeneous boundary magnetic field in the two-dimensional Ising model. They identified the transition that separates the regime where the interface is localized near the boundary from that where it propagates inside the bulk. Inspired by these results, we measured the interface tension by using multimagnetic simulations combined with parallel tempering to determine the phase transition and the location of the interface. Our results are in very good agreement with the theoretical predictions. Furthermore, we studied the spin-spin correlation function for which no analytical results are available.